Analisis dan Pemetaan Kualitas Air di Kecamatan Percut Sei Tuan Kabupaten Deli Serdang Sumatera Utara - Marbun, Sahala Fransiskus; Br Simatupang, Eliana Renintan; Ramadhani, Haniyah; Leirisa, Reva; Telaumbanua, Fausta John Aro; Hutauruk, Randy Marcel (Innovative: Journal Of Social Science Research, 2025)
Water quality is an important aspect in supporting public health and welfare. This study aims to map the distribution of water quality in Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, which is known to have several villages with indications of water pollution, such as changes in color to yellowish. This study uses a quantitative and qualitative approach, with data collection techniques in the form of measuring pH parameters and observing environmental conditions around water sources such as dug wells. The results of the analysis show that there is variation in water quality between villages; some meet clean water quality standards, while others indicate contamination due to agricultural activities, poor waste management, and household waste. The pH value of the water was measured and classified into acidic, neutral, and alkaline categories according to quality standards. Data visualization was carried out in the form of a water quality map using a cartographic approach and geographic information systems (GIS). These findings emphasize the importance of regular monitoring of water quality and the need for sustainable environmental management. According to Djamaluddin et al. (2019), the use of cartographic technology is effective in mapping water quality and supporting data-based policy making. This research is expected to be the basis for policy recommendations and increase public awareness in maintaining clean water quality in the area.